Expression of miR-93-5p in patients with esophageal carcinoma and its relationship with the curative effect and prognosis of radiotherapy - Chen, Lingzhi; Fan, Xinhua; Wang, Xiangming; Wu, Xianhua (Cellular and Molecular Biology, 2020)
This study aimed to investigate the expression of miR-93-5p in esophageal carcinoma-patients and its relationship with the curative effect and prognosis of radiotherapy. 102 patients with esophageal carcinoma treated in Yiwu Central Hospital from May 2013 to July 2015 were considered as the experimental group, and 89 healthy people for physical examination during the same period were selected as the control group. The expression of miR-93-5p in the serum of the two groups was compared. Based on the mean expression of miR-93-5p in serum, esophageal carcinoma patients were divided into high expression and low expression groups. Then the relationship between clinical-pathological characteristics and the expression of miR-93-5p was analyzed. The curative effect of radiotherapy in patients with esophageal carcinoma was evaluated, and the relationship between the expression of miR-93-5p, the curative effect of radiotherapy and the 3-year survival rate in patients with esophageal carcinoma was analyzed. The expression of miR-93-5p in the serum of the experimental group was significantly higher than that of the control group (P< 0.05); there was a significant correlation between the expression of miR-93-5p and pathological stage (P< 0.05). The expression of miR-93-5p in the effective radiotherapy group was significantly lower than that in the ineffective radiotherapy group (P< 0.05). ROC curve showed that the sensitivity and specificity of miR-93-5p in predicting radiotherapy response of esophageal carcinoma were 88.57 and 64.69% respectively, AUC was 0.864 (95%CI:0.791~0.936), P< 0.001; the 3-year survival rate of low expression group was significantly higher than that of high expression group (P< 0.05). In Conclusion, the expression of miR-93-5p was high in esophageal carcinoma patients, and the higher the expression, the worse the curative effect of radiotherapy and the worse the prognosis, which may be a new predictor of radiotherapy effect and prognosis in patients with esophageal carcinoma.